Traditional Chinese medicine injections: where we are after 80-year development - Wenwen Zheng; Yiyang Wu; Hanlu Gao; Defang Ouyang (BMC, 2022)
Abstract Traditional Chinese medicine (TCM) injection is the combination of modern pharmaceutical technology and traditional Chinese prescription, which was born in 1941 and played a great role in the backward medical conditions at that time. However, the debate over TCM injections has never stopped due to adverse drug reactions (ADRs). The regulation on TCM injections has been further strengthened since 2017, which has prompted many TCM injections to carry out re-evaluations on quality, safety, efficiency as well as pharmacoeconomics, which made significant changes and progress. This review presented an up-to-date analysis of the types, amounts, and ADRs of TCM injections based on the published data and literature. This review also summarized the potential reasons for the ADRs and re-evaluation strategies. This review will provide some useful clues for TCM injections and their clinical use.